Tableau de bord 1997 : follow-up to the conclusions of the Essen European Council on employment policies. (Employment and social affairs, 1997)
Summary: The purpose of this 1997 version of the tableau de bord (synoptic table) is to give a synoptic overview of the main employment policies and labour market measures in the Member States of the European Union. Its structure is based on the framework of the follow-up to the Essen council decisions of December 1994. The only structural modification to last year's tableau de bord has been to add a new section providing information on training and other labour market policies in favour of people with disabilities.